Dwarf minke whales (Balaenoptera acutorostrata) acoustic signals from the South Atlantic Ocean - Lis Bittencourt; Lis Bittencourt; Rafael Carvalho; Elitieri B. Santos-Neto; Tatiana L. Bisi; Tatiana L. Bisi; Jose Lailson-Brito; Jose Lailson-Brito; Alexandre F. Azevedo; Alexandre F. Azevedo (Frontiers in Marine Science, 2024)
At present, there are still populations of different balaenopterids that have never been acoustically recorded and observed simultaneously. In an opportunistic sighting of dwarf minke whales during winter in southeastern Brazil, we have registered six individuals and recorded over 200 acoustic signals. Signals were quantified and had their acoustic parameters extracted; the calling rate was estimated as the number of sounds per minute, and the repetition rate was estimated as the number of calls of the same type emitted per minute. Four call types were described: Ba1, Ba2, Ba3 and Ba4. The most common and distinctive call was the Ba1, composed of three components: one had a peak frequency of 615.0 ± 189.8 Hz, and the other had peak frequencies of 1632.0 ± 191.5 and 5038.2 ± 195.1 Hz. Ba1 repetition varied from 2.4 to 11.1 repetitions/min. Ba2 was the second most common call with a peak frequency of 485.2 ± 421.9 Hz. The total calling rate varied from 4.4 to 11.1 calls/min. The signals are in the same frequency range reported for other areas but contain different structures.